School Principals’ Strategies for Enhancing Teachers’ Professional and Pedagogical Competencies - Chusniah, Chusniah; Hamzah, Akhmad Fauzi; Asr Hismsyah, Unun Zumairoh (Jurnal Inovatif Manajemen Pendidikan Islam, 2025)
In Sampang Regency, Madura, the quality of learning remains relatively low, as indicated by weak lesson planning and implementation by teachers. This condition is closely related to the limited mastery of professional and pedagogical competencies, particularly in the development of teaching materials, the application of active learning strategies, and the use of technology. This phenomenon underscores the strategic role of school principals in enhancing teachers’ capacity through effective leadership. This study aims to analyze the strategies employed by the principal of SMAI Salafiyah Sreseh, Sampang, Madura, in developing teachers’ professional and pedagogical competencies. The research adopts a descriptive qualitative method with data collected through observation, interviews, and documentation. The findings reveal that the principal implements several strategies, including continuous professional training, technology integration in teaching, strengthening teacher collaboration, and regular supervision. Training and supervision have proven effective in enhancing teachers’ skills in designing and delivering instruction tailored to students’ needs. Meanwhile, technology facilitates more interactive and adaptive learning experiences. Teacher collaboration fosters creativity and professional growth. Overall, these strategies contribute to improving the quality of instruction, student motivation, and the creation of an innovative educational climate. The principal’s leadership in developing teacher competencies plays a critical role in addressing educational challenges and preparing students to meet contemporary demands.